2008
DOI: 10.1103/physrevlett.101.046801
|View full text |Cite|
|
Sign up to set email alerts
|

Highly Conductive Molecular Junctions Based on Direct Binding of Benzene to Platinum Electrodes

Abstract: Highly conductive molecular junctions were formed by direct binding of benzene molecules between two Pt electrodes. Measurements of conductance, isotopic shift in inelastic spectroscopy, and shot noise compared with calculations provide indications for a stable molecular junction where the benzene molecule is preserved intact and bonded to the Pt leads via carbon atoms. The junction has a conductance comparable to that for metallic atomic junctions (around 0:1-1G 0 ), where the conductance and the number of tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
298
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 304 publications
(326 citation statements)
references
References 24 publications
26
298
2
Order By: Relevance
“…In this sense, it would be highly desirable to widen the list of materials that can be used as electrodes. 2,7 Carbon is obviously a good candidate as an electrode material in molecular electronics because it offers the possibility to contact a variety of molecules without the need of anchoring groups, it is also relatively inert, and it forms structures like graphene 8,9 and nanotubes 10 that can be used as nanoelectrodes.…”
mentioning
confidence: 99%
“…In this sense, it would be highly desirable to widen the list of materials that can be used as electrodes. 2,7 Carbon is obviously a good candidate as an electrode material in molecular electronics because it offers the possibility to contact a variety of molecules without the need of anchoring groups, it is also relatively inert, and it forms structures like graphene 8,9 and nanotubes 10 that can be used as nanoelectrodes.…”
mentioning
confidence: 99%
“…14 IETS measurements using 12 C 6 H 6 and 13 C 6 H 6 molecules found isotropic effects were present in the resultant frequency spectra. 60 IETS can therefore be considered to be a powerful method for identifying single molecules (both in SMJs and otherwise); however, unlike IR and Raman spectroscopy, it is unclear how the selection rule for the vibration modes can be determined. Nevertheless, it has been experimentally found that when a molecule has a high symmetry, the vibration modes obtained by IETS are similar to those obtained by Raman spectroscopy.…”
Section: Single-molecule Analysis Methodsmentioning
confidence: 99%
“…65 Furthermore, platinum electrodes would easily adsorb hydrogen molecules. 60 Lastly, for single gold atom junctions, electrons flow through the orbitals of these junctions, which are composed of the 6s orbital of the gold atoms. Therefore, in single gold atom junctions, T is one.…”
Section: Single-molecule Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations